ADAM10 new selective inhibitors reduce NKG2D ligand release sensitizing Hodgkin lymphoma cells to NKG2D-mediated killing. (3rd May 2016) - Zocchi, Maria Raffaella; Camodeca, Caterina; Nuti, Elisa; Rossello, Armando; Venè, Roberta; Tosetti, Francesca; Dapino, Irene; Costa, Delfina; Musso, Alessandra; Poggi, Alessandro
ABSTRACT: Hodgkin lymphoma (HL) resistant to conventional therapies is increasing, making of interest the search for new schemes of treatment. Members of the "A Disintegrin And Metalloproteases" (ADAMs) family, mainly ADAM10 or ADAM17, have been proposed as therapeutic targets in solid tumors and some ADAMs inhibitors have been shown to exert antitumor effects. We have previously described an overexpression of ADAM10 in HL, together with increased release of NKG2D ligands (NKG2D-L) and reduced activation of effector T lymphocytes with anti-lymphoma capacity. Aim of the present work was to verify whether inhibition of ADAM10 in HL cells could restore the triggering of NKG2D-dependent anti-lymphoma T cell response. As no selective ADAM10 blockers have been reported so far, we synthesized the two hydroxamate compounds LT4 and MN8 with selectivity for ADAM10 over metalloproteases (MMPs), LT4 showing higher specificity for ADAM10 over ADAM17. We show that (i) HL lymph nodes (LN) and cultured HL cells express high levels of the mature active membrane form of ADAM10; (ii) ADAM10 is the major sheddase for the NKG2D-L in HL cells; (iii) the new LT4 and MN8 compounds strongly reduce the shedding of NKG2D-L by HL cell lines and enhance the binding of NKG2D receptor; (iv) of note, these new ADAM10 inhibitors increase the sensitivity of HL cell lines to NKG2D-dependent cell killing exerted by natural killer and γδ T cells. Overall, the biologic activity of LT4 and MN8 appears to be more potent than that of the commercial inhibitor GI254023X.